Drug metabolism in liver disease - Zgheib, Nathalie; Branch, Robert (Henry Stewart Talks, 2016)
Drug metabolism, Liver disease and drug clearance, Mechanistic explanations, Intact hepatocyte hypothesis, Sequential progressive model of liver disease, Liver disease etiology, Liver disease severity, Epigenetics, Biomarkers
Reviewed at 2020/08/12